Goldfish Breeding Business Development in Kampung Wouma, Wamena Kota District - Ayub Tanudy (PT Inovasi Pratama Internasional, 2024)
The potential for natural resources in the Wamena City District area is very abundant. One of the businesses being developed by the community there is goldfish farming which has been started since 2015. The aim of this study for analyze how the carp business is developing in Wouma village, Wamena city district. Method​ Qualitative is used to explain the development of the carp farming business including the condition of the breeder, the problems faced by the breeder including business capital, labor, production, price and other factors that must be considered for development. business​ fish​ m a s. Meanwhile, the analysis method quantitative used for count level farmer's net income with profit calculation. The amount of goldfish breeder capital varies, depending on the condition of the breeder. The average capital used to start a goldfish farming business ranges between Rp. 8,500,000 to Rp. 10,000,000. Of the 10 respondents studied, the number of workers needed to develop goldfish was 34 people. Generally, these breeders are heads of families with junior high school and senior high school education. Good price conditions will provide benefits for goldfish production and have a positive influence on breeders to increase their production, because prices directly affect income levels. Until 2021, the price of carp will reach Rp. 35,000 per kg, in 2022 the price of goldfish will reach IDR. 38,000 per kg and in 2023 the price of goldfish will reach IDR. 40,000 per kg. Furthermore, the goldfish production produced by breeders has increased from year to year. Carp production will range from 1,040 kg to 1,760 kg until 2023. Research shows goldfish sales don't meet consumer demand, with respondent 5 earning the least and respondent 3 earning the most.